Clinical significance of hemostatic parameters in the prediction of type 2 diabetes mellitus and diabetic nephropathy - 钱科威; 顾晓琦; 孙晓红; 钟梦丹; 崔艳; 李红; 戴强; 杨敏 (Linchuang shenzangbing zazhi)
Objective This study was aimed at evaluating the predicting significance of hemostatic parameters for type 2 diabetes mellitus(T2 DM) and diabetic nephropathy(DN). Methods A total of 96 patients with T2 DM were divided into two groups, T2 DM without complications(52 cases) and T2 DM with nephropathy(44 cases); at the same time, 50 cases of healthy control people admitted simultaneously with corresponding sex and age. Hematologic parameters before treatment were measured in 96 T2 DM patients and 50 healthy controls, so as to evaluate the risk factors and their predictive ability. Results The T2 DM patients without complications exhibited significantly different activated partial thromboplastin time(APTT), platelet(PLT), and D-dimer(D-D) levels, compared with the controls(P<0.01). Fibrinogen(FIB), PLT, and D-D increased in DN patients compared with those without complications(P<0.05). Both APTT and PLT were the independent risk factors for T2 DM(OR: 1.743 and 1.238, respectively, P<0.01), and FIB and PLT were the independent risk factors for DN(OR: 1.642 and 1.317, respectively, P<0.01). The areas under ROC curve(AUC) of APTT and PLT were 0.601 and 0.642, respectively, with low sensitivity in predicting T2 DM. AUC of FIB was 0.876 with high sensitivity(84%) and specificity(77%) for DN, and that of PLT was 0.571, with sensitivity of 61% and specificity of89% based on the cutoff values of 3.15 g/L and 245×10~9/L, respectively. When combining FIB and PLT, the predicting ability increased(AUC: 0.887, 95%CI: 0.841～0.937, sensitivity: 91%, specificity: 74%). Conclusions Hemostatic parameters have a low predicting value for T2 DM, whereas fibrinogen is the independent risk factor with high predicting power for DN in patients with type 2 diabetes mellitus.